2007
DOI: 10.1242/jeb.002881
|View full text |Cite
|
Sign up to set email alerts
|

Maximum cardiac performance and adrenergic sensitivity of the sea bassDicentrarchus labraxat high temperatures

Abstract: -1 adrenaline at 18°C and 10-50·nmol·l -1 adrenaline at 22°C. We show that the sea bass, which lacks a coronary arterial oxygen supply to the ventricle, has a powerful heart. Its maximum performance is comparable to a salmonid heart, as is the modest stimulatory effect of adrenaline at high temperature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 55 publications
1
14
0
Order By: Relevance
“…hematocrit. It also indicates other regulation factors, such as gas diffusion distance, total respiratory surface area, heart rate, cardiac output and cardiac stroke volume may be more important for oxygen transport at high temperature (Saroglia, Cecchini, Terova, Caputo, & De Stradis, 2000;Saroglia, Terova, Stradis, & Caputo, 2002;Sollid et al, 2005;Sollid & Nilsson, 2006;Dowd et al, 2006;Farrell, Axelsson, Altimiras, Sandblom, & Claireaux, 2007;Farrell, Eliason, Sandblom, & Clark, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…hematocrit. It also indicates other regulation factors, such as gas diffusion distance, total respiratory surface area, heart rate, cardiac output and cardiac stroke volume may be more important for oxygen transport at high temperature (Saroglia, Cecchini, Terova, Caputo, & De Stradis, 2000;Saroglia, Terova, Stradis, & Caputo, 2002;Sollid et al, 2005;Sollid & Nilsson, 2006;Dowd et al, 2006;Farrell, Axelsson, Altimiras, Sandblom, & Claireaux, 2007;Farrell, Eliason, Sandblom, & Clark, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Mendonça and Gamperl (Mendonça and Gamperl, 2009) showed that the winter flounder heart is not dependent upon adrenergic stimulation at rest, and only reported increases of 6% in V S and 10% in Q following the simultaneous injection of 0.2 and 0.4gkg -1 of AD and noradrenaline at 8°C, respectively. Maximum adrenergic stimulation (up to 500nmoll -1 ) has no effect on either heart rate or maximum Q, and only a modest (10-15%) positive inotropic effect on power output of the in situ sea bass (Dicentrarchus labrax) heart at 18 and 22°C (Farrell et al, 2007). Finally, Lague et al (Lague et al, 2012) report that AD and noradrenaline concentrations as high as 5ϫ10 -6 moll -1 have no effect on function of the 22°C in situ tilapia (Oreochromis hybrid) heart under conditions of normoxia, hypoxia or acidosis.…”
Section: Cardiac Function and Adrenergic Stimulationmentioning
confidence: 95%
“…However, the apparent lack of myocardial responsiveness to adrenaline in cod may be due to the fact that only a single experimental temperature (10°C) has been examined to date. For example, research on other teleosts indicates that acclimation to 'warm' temperatures or those within a fish's optimal thermal range may reduce myocardial adrenergic sensitivity and/or adrenoreceptor density (Graham and Farrell, 1989;Keen et al, 1993;Shiels et al, 2003;Farrell et al, 2007). Thus, by examining the effects of adrenergic stimulation on maximum cardiac performance at several temperatures (0, 4 and 10°C), we were able to further evaluate what role circulating catecholamines play in supporting cod cardiac performance, and indeed, whether this species differs from other teleosts in this regard.…”
Section: Introductionmentioning
confidence: 99%
“…From the remaining fish, an in situ perfused heart preparation modified from Farrell et al (Farrell et al, 2007) was used to assess the maximum cardiac flow-generating capacity at 5, 12 and 18°C (three fish from each of the two replicate tanks, N=6 per experimental group). A halibut Ringer's solution (Rönnestad et al, 2000) containing isoprenaline (200 nmol l ; for maximum adrenergic stimulation) was used to perfuse the heart preparation, which was immersed in a saline-filled thermostat-controlled bath.…”
Section: Research Articlementioning
confidence: 99%